Study on Breast Cancer Patients and Some Variables in Babylon Province (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study included 100 women with breast cancer in Babylon province for six months at Morjan Teaching Hospital in the Department of Oncology The study showed that the most age group with breast cancer in the age group of 40 to 49 years, where they accounted for 25% of the proportions of patients It was also found in the study that the most affected women lived in the center of the city (Urban Area), where they accounted for 60% of the total patient, Most of them were housewives (not working outside the home), with 77%,And 79% of them were first infected with the disease, And 45% of them had a malignant type of tumor